Solving dilemmas through experience - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Endangered species, decreasing biodiversity, threatened wetlands, and lakes that are running dry are widely acknowledged problems. Many policymakers and experts are convinced that they will find the one way forward to nature conservation. This...